Selfhood and appearing : the intertwining - Mensch, James R. (Studies in Contemporary Phenomenology, 2018)
What is the relation between our selfhood and appearing? Our embodiment positions us in the world, situating us as an object among its visible objects. Yet, by opening and shutting our eyes, we can make the visible world appear and disappear-a fact that convinces us that the world is in us. Thus, we have to assert with Merleau-Ponty that we are in the world that is in us: the two are intertwined. Author James Mensch employs the insights of Jan Patočka's asubjective phenomenology to understand this double relationship of being-in. In this volume, he shows how this relation constitutes the reality of our selfhood, shaping our social and political interactions as well as the violence that constantly threatens to undermine them.